The Use of Carnival Features for the Promotion of a New African Image in the Novels of Ouologuem, Kourouma and Labou Tansi - Bakurumpagi , Victoria (African Journal of Education,Science and Technology (AJEST), 2018)
In this article, after defining the concepts of the Negro myth and the carnival, I show what these three novels have in common: giving the impression that the negative image given to Black Africa by Europe was justified while at the same time giving a fresh interpretation of many of the prejudices against the black man since slave trade. The article shows that the creation of African imaginary territories and the dual language characteristic of the carnival are intended to promote a new African image. In order to arrive at the interpretation given here, I used the postcolonial theory as described by Edward Said Culture and imperialism and the deconstructive criticism as defined by Atkins Douglas in Reading deconstruction and deconstructive reading.